Câu 1: Phân tích thành nhân tử
ab(x^2+y^2)+xy(a^2+b^2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\left(x+y+z\right)^3-\left(x+y-z\right)^3-\left(x-y+z\right)^3-\left(-x+y+z\right)^3\)
\(=\left(a+b+c\right)^3-a^3-b^3-c^3\)(\(a=-x+y+z,b=x-y+z,c=x+y-z\))
\(=\left(b+c\right)^3+3a\left(a+b+c\right)\left(b+c\right)-\left[\left(b+c\right)^3-3bc\left(b+c\right)\right]\)
\(=3\left(b+c\right)\left(a^2+ab+ac+bc\right)\)
\(=3\left(a+b\right)\left(b+c\right)\left(c+a\right)\)
\(=24xyz\)
a, \(VP=\frac{35xy^2}{65y^2}=\frac{5y^2.7y}{5y^2.13}=\frac{7y}{13}=VT\)( đpcm )
b, \(VP=\frac{x^2-6x-7}{x+1}=\frac{\left(x-7\right)\left(x+1\right)}{x+1}=x-7\)
\(=\frac{\left(x-7\right)\left(x-1\right)}{x-1}=\frac{x^2-8x+7}{x-1}=VT\)( đpcm )
x2 - y2 + a2 - b2 + 2ax + 2by
= ( x2 + 2ax + a2 ) - ( b2 - 2by + y2 )
= ( x + a )2 - ( b - y )2
= ( x + a - b + y ) ( x + a + b - y )
x3 - 2x2 - 6x + 27
= ( x - 3 )3
\(ab\left(x^2+y^2\right)+xy\left(a^2+b^2\right)=abx^2+aby^2+a^2xy+b^2xy\)
\(=ax\left(bx+ay\right)+by\left(ay+bx\right)=\left(ax+by\right)\left(ay+bx\right)\)